2021
DOI: 10.1039/d1ob01829a
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-mediated decarboxylative alkylation of 2-pyridone derivatives via a C3-selective C–H functionalization

Abstract: A direct C–H functionalization approach to access C3-alkylated 2-pyridone derivatives is reported. This study utilizes N-hydroxyphthalimide (NHPI) esters of various carboxylic acids as sources for alkyl radicals by reductive cleavage...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…5 Yamakawa et al reported for the first time diverse highly reactive alkylating reagents for the C3-selective radical C–H trifluoromethylation 6 of 2-pyridone, including α-bromo carbonyl, 7 2-substituted diethyl malonates, 8 xanthate, 9 and NHPI esters. 10 Due to the highest electron deficiency at the C6 position of the 2-pyridone ring, achieving selective C–H functionalization at this site requires different strategies compared to those for other positions. Nakao and Hiyama successfully achieved direct C6-selective alkylation with unactivated alkenes using Ni/Al cooperative catalysis.…”
mentioning
confidence: 99%
“…5 Yamakawa et al reported for the first time diverse highly reactive alkylating reagents for the C3-selective radical C–H trifluoromethylation 6 of 2-pyridone, including α-bromo carbonyl, 7 2-substituted diethyl malonates, 8 xanthate, 9 and NHPI esters. 10 Due to the highest electron deficiency at the C6 position of the 2-pyridone ring, achieving selective C–H functionalization at this site requires different strategies compared to those for other positions. Nakao and Hiyama successfully achieved direct C6-selective alkylation with unactivated alkenes using Ni/Al cooperative catalysis.…”
mentioning
confidence: 99%